Assessing Levels and Forms of Incivility and Deliberative Quality in Online Discussions on COVID-19: A Cross-Platform Analysis - Schroll, Cornelia; Huber, Brigitte (Frontiers in Political Science, 2022)
Studying incivility in online discussions is a crucial research endeavor, especially in light of a pandemic, as user comments have been shown to be an important source of information and basis for opinion formation. Scholars are increasingly interested in studying incivility from a comparative perspective. This study contributes to this strand of literature by investigating incivility in user comments on the news website and Facebook site of the Austrian newspaper Der Standard. A content analysis (N = 240) was employed to identify forms and levels of incivility in user comments on topics related to COVID-19. Results show Facebook comments to be significantly less uncivil than user comments on the newspaper’s website. Moreover, differences regarding the prevalence of the dimensions of incivility on the two platforms were identified. Finally, results suggest that incivility does not necessarily go hand in hand with lower levels of deliberative quality. Implications for news organizations and democracy are discussed.